Non-invasive imaging techniques in patients with coronary chronic total occlusions: A key for successful diagnosis, revascularization, and post-intervention outcomes - Marta Mielniczuk (Cardiology Journal, 2023)
Coronary chronic total occlusions (CTOs) are a common finding on coronary angiograms of patients with coronary artery disease, with an incidence ranging from 15% to 25%. Despite this high incidence, the proper treatment strategy in those patients often remains unclear. There are some observational studies suggesting that successful revascularization of a CTO can reduce angina symptoms, improve quality of life, improve the left ventricular ejection fraction, and lower mortality. However, not all patients will benefit from revascularization. Pre-procedural assessment of left ventricular function, ischemic burden, and viability seems to be crucial for a good outcome of the revascularization. The aim of this review is to compare currently available non-invasive imaging modalities with regard to utility in evaluation of patients with CTOs.